Bacterial Conjunctivitis and Use of Antibiotics in Dhulikhel Hospital - Kathmandu University Hospital - Sthapit, P R; Tuladhar, N R; Marasini, S; Khoju, U; Thapa, G (Kathmandu University Medical Journal, 2012)
Background Acute Infective Conjunctivitis may be due to viral or bacterial infection; though it is usually self limiting, topical antibiotics are often prescribed for rapid recovery. Objectives This study aims to find out prevalence of bacterial infection among cases of acute infective conjunctivitis and to determine their in-vitro antibacterial susceptibilities to commonly used antibacterial agents and to find out whether the rampant use of topical antibiotics are at all necessary or justified. Methods A prospective analytical study conducted over a period of two years on clinically diagnosed cases of Acute Infective Conjunctivitis. Isolation and identification of microorganisms by culture and antimicrobial susceptibility test were done on conjunctival swabs from 65 patients. Results A total of 65 patients were included where children (one month to 10 years old) accounted for the commonest age group (35.4%).On Gram’s Stain, 90.8% were negative for pus cells or micro organisms. Gram positive cocci were found in 6.2% of cases. On culture, bacterial growth was seen in 11 cases (18.9%) among which Streptococcus pneumonia was seen in seven cases (10.8%).The analysis on in-vitro susceptibility testing showed that Chloramphenicol and Gentamicin were the most sensitive (78.6% of samples) drugs for conjunctivitis. ConclusionOphthalmic antibiotics should be prescribed judiciously in acute infective conjunctivitis even for suspected bacterial cases; since it is found to resolve spontaneously without any serious complications. Chloramphenicol and Gentamicin are drugs of choice if at all required.DOI: http://dx.doi.org/10.3126/kumj.v9i2.6292 Kathmandu Univ Med J 2011;9(2):69-72